PENGARUH BUDAYA DAN KOMITMEN ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN (STUDI PADA PT. ASTRA INTERNATIONAL, Tbk – HONDA SALES OPERATION KANWIL PALEMBANG) - HENDRA HADIWIJAYA; AGUSTINA HANAFI (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2013)
ABSTRACT Motivation is important because the motivation of every employee is expected to work hard to achieve organizational goals. This study analyzes the factors that influence culture and organizational commitment on employee motivation at PT. Astra International, Tbk – Honda Sales Operation Kanwil Palembang. The problems of the researcher is to knowIs there any influence of organizational culture on employee motivation and organizational commitment influence on employee motivation and to determine which variables most influence on employee motivation PT. Astra International, Tbk- Honda Sales Operation Kanwil Palembang. This study develops three hypotheses in order to answer the problems that exist. This study conducted a census of 170 people while as many as 162 questionnaires were returned. The respondent is an employee of PT. Astra International, Tbk- Honda Sales Operation Kanwil Palembang. This study uses Structural Equation Modeling(SEM) using Lisrel programas ananalysis tool. Results of data analysis showed that the hypothesis can be accepted. The results proved that organizational culture has apositive and significant impacton employee motivation with at-value>1.96 is equal to11.54 with an estimated value of 0.82 and acommitment to the organization also has a positive effect on the motivation of working with t-value of 16,42 with an estimated value of 1.02. Organizational commitment is the most significan t variable with a value of 11.54t- value in comparison with the value oforganizational culturet-value 11.54 on employee motivation PT. Astra International, Tbk- Honda Sales Operation Kanwil Palembang. Based on the results of this study provide the oretical implications of a strong influence on employee motivation such as organizational culture and organizational commitment. managerial implications of this research is the PT. Astra International, Tbk- Honda Sales Operation Kanwil Palembang. need to pay attention and make employees become part of the organization because of the presence of emotional or psychological bond that employee shave the awareness and commitment to the organization is indeed to be done.